2015
DOI: 10.1182/asheducation-2015.1.340
|View full text |Cite
|
Sign up to set email alerts
|

Management of symptoms in polycythemia vera and essential thrombocythemia patients

Abstract: The BCR-ABL-negative myeloproliferative neoplasms (MPNs) are clonal stem cell derived malignancies, which include polycythemia vera (PV), essential thrombocythemia (ET), and myelofibrosis (MF). The MPNs are characterized by dysregulated JAK-STAT signaling pathways. PV and ET are associated with an increased risk of thrombo-hemorrhagic complications, risk of progression to MF and leukemia. Presentation of patients with PV and ET is variable and usually as a result of abnormal full blood count indices (raised he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 63 publications
0
18
0
4
Order By: Relevance
“…2,3 Published studies in women with ET have primarily focused on the outcomes of live birth rate and pregnancy complications, 4-8 with little data available on the absolute risk of VTE (deep vein thrombosis [DVT] and pulmonary embolism [PE]) during pregnancy or the 6-week postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Published studies in women with ET have primarily focused on the outcomes of live birth rate and pregnancy complications, 4-8 with little data available on the absolute risk of VTE (deep vein thrombosis [DVT] and pulmonary embolism [PE]) during pregnancy or the 6-week postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by several authors who concluded that the presence of this mutation may play a role in the development of vascular complications. [22,25,26] These results show that Jak2V617 mutation would affect the severity of signs and occurrence would be a factor of progressive complications.…”
Section: Discussionmentioning
confidence: 75%
“…Proposed mechanisms are increased blood viscosity (increased number of clonal cells), easy activation of platelets, erythrocyte, and plate abnormalities that were found to be associated with JAK-2 V617F mutation and endothelium impairment. [4] Accordingly, JAK-2 V617F mutation is confirmed as an independent risk factor for thrombosis. [4] Dentali et al investigated the frequency of PV in a series of 706 patients with cerebral vein thrombosis (CVT) and the frequency of CVT in a cohort of 2,143 MPNs (735 with PV) patients.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Accordingly, JAK-2 V617F mutation is confirmed as an independent risk factor for thrombosis. [4] Dentali et al investigated the frequency of PV in a series of 706 patients with cerebral vein thrombosis (CVT) and the frequency of CVT in a cohort of 2,143 MPNs (735 with PV) patients. [5] The incidence of MPN in CVT patients was 3.8%; however, among 735 PV patients, only 5 (0.7%) were documented to have CVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation